PET CT Imaging with FDG in the Therapeutical Management of Locally Advanced Cervical Cancer Diagnosed in a 43-Year-Old Patient: Case Report and Review of the Literature - Ottó Molnar; Simona Mihuțiu; Oreste Mihai Straciuc; Alexandra Vesa; Liviu Lazar (Biomedicines)
Background: Cervical cancer is the most important cancer type found in women throughout the world. Numerous research studies are being performed to investigate the effectiveness of different strategies for the imaging and treatment of locally advanced cervical cancer, which are showing favorable outcomes. Brachytherapy is characterized by the application of very high radiation doses to target tumor cells with the least exposure to normal tissues. Methods: In the present case study, we report a 43-year-old female patient suffering from cervical cancer belonging to urban origin, with no personal pathological history, who presented herself to the gynecology department of the Bihor County Emergency Clinical hospital with vaginal bleeding. The histopathological examination of the cervix showed squamous cell carcinoma. The treatment was performed with neoadjuvant chemotherapy and concurrent chemoradiotherapy. Results: According to the clinical and histopathological examination, a diagnosis of non-keratinizing squamous carcinoma of the uterine cervix at FIGO stage III C1 was established. Radio-chemotherapy was performed, as well as periodic imaging assessments with a CT of the chest, pelvis, and abdomen, without local and distant relapse. FDG PET imaging was performed for the management and follow-up of cervical cancer by retrieving the SUVmax value. Conclusions: The post-therapeutic complications are represented by the vaginal stenosis installed 6 months after the end of the radiotherapeutic treatment.